Early Versus Late Endotracheal Intubation in Subjects with COVID-19 Pneumonia Treated with High-Flow Oxygen: A Retrospective Observational Study - Nadeem, Rashid; Alheraki, Muhannad; Dar, Farooq; Hussein, Karim S; Mirza, Hina; Aijazi, Ishma; ElZeiny, Moatz G; Awadh, Neama A; Osman, Hadeel; Albwidani, Rawan (Curēus (Palo Alto, CA), 2023)
The availability of high-flow oxygen (HFO) machines allowed patients with COVID-19 pneumonia to be comfortably treated for longer periods of time until endotracheal intubation became inevitable. Patients treated with invasive mechanical ventilation (MV) preceded by HFO treatment may continue to progress and die. Hence there is a belief in physicians that patients treated with HFO might have delayed invasive MV.INTRODUCTIONThe availability of high-flow oxygen (HFO) machines allowed patients with COVID-19 pneumonia to be comfortably treated for longer periods of time until endotracheal intubation became inevitable. Patients treated with invasive mechanical ventilation (MV) preceded by HFO treatment may continue to progress and die. Hence there is a belief in physicians that patients treated with HFO might have delayed invasive MV.The study was conducted as a retrospective review of subjects with confirmed COVID-19 admitted to the Dubai Hospital ICU. Study variables included time to intubation, duration of HFO, and cumulative duration of tachypnea and tachycardia while on HFO usage. Early intubation was defined as within 24 hours of the start of HFO, and late intubation was defined as after seven days on HFO. Groups were compared for outcome measures; mortality and length of stay (LOS) in the ICU and hospital.METHODSThe study was conducted as a retrospective review of subjects with confirmed COVID-19 admitted to the Dubai Hospital ICU. Study variables included time to intubation, duration of HFO, and cumulative duration of tachypnea and tachycardia while on HFO usage. Early intubation was defined as within 24 hours of the start of HFO, and late intubation was defined as after seven days on HFO. Groups were compared for outcome measures; mortality and length of stay (LOS) in the ICU and hospital.Clinical outcomes of mortality and LOS in ICU and hospital were not significantly different among patients intubated early versus late. Duration of tachypnea and tachycardia was also not different comparing patients intubated early versus late.RESULTSClinical outcomes of mortality and LOS in ICU and hospital were not significantly different among patients intubated early versus late. Duration of tachypnea and tachycardia was also not different comparing patients intubated early versus late.There was no significant difference in clinical outcomes in patients intubated early versus late in patients treated with HFO for COVID-19 pneumonia.CONCLUSIONThere was no significant difference in clinical outcomes in patients intubated early versus late in patients treated with HFO for COVID-19 pneumonia.